Causes and risk factors for an acute kidney injury outbreak among children in The Gambia, June - September 2022: A case-cohort study. - Mustapha Bittaye; Jayne Byakika-Tusiime; Lionel Adisso; Boris I Pavlin; Michel Muteba; Anna H Jammeh; Ifeanyi Livinus Udenweze; Amadou Woury Jallow; Nuha Fofana; Momodou Kalisa; Sharmila Lareef; Kassa Mohammed Abbe; et al. (PLoS ONE)
Introduction Between June and September 2022, an outbreak of acute kidney injury (AKI) occurred in The Gambia among children, with 82 cases and 66 deaths recorded. Medicines taken by children with AKI were found to contain unacceptable amounts of diethylene glycol (DEG) and ethylene glycol (EG). The objective of the study was to establish the likely cause of the AKI outbreak and associated risk factors. Materials and methods A case-cohort study was conducted in six of the seven regions of The Gambia. Cases were children eight years or younger, residing within the six regions in the study period and diagnosed with AKI within that period. Controls were children in the same age range as cases and residing within the same neighborhood as cases but without a diagnosis of AKI. Three hundred twenty-one children were recruited for the sub-cohort from which controls were selected. Data were analyzed using Marginal Structural Models for a point treatment with the inverse probability of treatment weights estimator. Multivariable logistic regression was used to identify risk factors for AKI using a 5% level of significance in the final model. Results Sixty-three cases and 258 controls were enrolled into the study. Of the 63 cases, 58 were confirmed and five were suspected cases. AKI among the children was causally associated with ingestion of adulterated medicine(s) (OR = 1.76 (1.60-1.92); p < 0.0001). Risk factors of AKI were the ingestion of adulterated medicine(s), concomitant medicines, and being of a younger age. Conclusion The acute kidney injury outbreak that occurred among children in The Gambia in the period June through September 2022 was causally associated with the ingestion of adulterated medicines. The risk was increased by consumption of concomitant medicines and being of a younger age. DEG adulteration of paediatric medicines has been an all-too -common event in multiple countries.